Nursing problems of a 9-year-old boy with attention deficit hyperactivity discorder who is musturbating - Pawełko, Agnieszka; Ciechacka, Maria (Journal of Education, Health and Sport, 2025)
Effective care for a patient with ADHD requires a comprehensive approach that includes educating the patient and their family, as well as applying appropriate therapeutic techniques. Reducing aggression and frustration relies on calm conversations and finding ways to release energy. Improvement in concentration and motor coordination is possible through suitable exercises and therapeutic methods. Stabilization of mood and improvement in sleep quality necessitates psychotherapeutic support, physical activity, and education on healthy sleep principles.